Natural Resources and Financial Security: The Synergy of Sustainable Development Economics and Artificial Intelligence - Petrukha, Serhii; Petrukha, Nina; Stoliarenko, Olena; Ortina, Hanna; Ортіна, Ганна Володимирівна; Stuzhuk, Ruslan; Plakhotnii, Dmytro (My University, 2025)
Major transformations are decisively reshaping the intersection of financial markets, artificial intelligence, and natural resource economics. The emergence of the digital age has resulted in a previously unheard-of degree of connectivity, information accessibility, and sophisticated computing power, radically altering traditional procedures and spawning novel paradigms. The proposed study aims to enrich the sustainable development literature by outlining and systematizing emerging patterns and trends in sustainable natural resources management and financial security enhancement, based on AI synergetic influence on sustainable development economy functioning. Based on the method of narrative review, theoretical provisions, practical implications, and cases are investigated, representing a systemic picture of intertwining and strong correlations between sustainable finance and sustainable management of natural resources in the landscape of continuous AI solutions development. The paper outlines the patterns of relation between sustainable development, digital transformation, and financial concerns, in particular within the sustainable finance paradigm. It is demonstrated that AI plays a key role in the green economy to generate monetary and environmental rewards, strengthening nation-state financial security. The patterns revealed in the process of review demonstrate that AI offers both financial and environmental advantages, being a potent tool for international decision-making, risk management, and investment in environmentally friendly businesses, climate investing, and renewable energy projects.
Keywords: Sustainable finance; AI-driven decisions; Sustainable economy; Financial security